2019
DOI: 10.2147/cmar.s198714
|View full text |Cite
|
Sign up to set email alerts
|

<p>Serum hepatitis B viral (HBV) DNA is a predictive biomarker for survival in non-small cell lung cancer patients with chronic HBV infection</p>

Abstract: Purpose: To study the association between pretreatment serum hepatitis B viral (HBV) DNA copy numbers and clinical outcome of non-small cell lung cancer (NSCLC) patients with chronic HBV infection. Patients and methods: We retrospectively evaluated the medical records of NSCLC HBV (+) patients between January 2008 and December 2010. The HBV DNA copy numbers and other prognostic factors including albumin (ALB), C-reactive protein (CRP), platelet, neutrophil–lymphocyte ratio (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…In a similar study, Fu et al [50] reported that high pretreatment serum HBV DNA copy numbers could act as a negative prognostic marker for survival among NSCLC patients with chronic HBV infection. Conversely, Zou et al [51] found that among esophageal cancer patients, those who were HBsAg-positive had a more favorable OS (HR, 0.80; 95% CI, 0.65-0.95; P = 0.020) than those who were HBsAg-negative.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a similar study, Fu et al [50] reported that high pretreatment serum HBV DNA copy numbers could act as a negative prognostic marker for survival among NSCLC patients with chronic HBV infection. Conversely, Zou et al [51] found that among esophageal cancer patients, those who were HBsAg-positive had a more favorable OS (HR, 0.80; 95% CI, 0.65-0.95; P = 0.020) than those who were HBsAg-negative.…”
Section: Discussionmentioning
confidence: 89%
“…In a similar study, Fu et al . [ 50 ] reported that high pretreatment serum HBV DNA copy numbers could act as a negative prognostic marker for survival among NSCLC patients with chronic HBV infection. Conversely, Zou et al .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, epidemiological evidence demonstrated a potential association between HBV infection and extrahepatic cancer risk, which includes gastrointestinal cancers, head and neck cancer, cervical cancer, non-Hodgkin lymphoma, breast cancer, and nonsmall cell lung cancer (NSCLC) (13,14,(35)(36)(37)(38)(39) (Figure 1). Notably, HBV infection status can not only increase the extrahepatic cancer risk but can also significantly influence subsequent long-term survival patterns (40)(41)(42)(43)(44)(45). However, a multi-center study demonstrated that a large proportion of patients with newly diagnosed cancer and concurrent HBV were unaware of their viral infection at the time of cancer diagnosis (46).…”
Section: Chronic Hepatitis B In Extrahepatic Cancer Riskmentioning
confidence: 99%
“…Combining HBV infection status with peripheral blood indicators, clinicians could obtain more precise survival predictions in this subpopulation. Serum HBV DNA levels could also be an independent prognostic factor in patients with NSCLC (41). HBV infection was recently associated with NSCLC immune expression (112,113).…”
Section: Lung Cancermentioning
confidence: 99%